Результаты исследования системы пневматического рессорного подвешивания транспортного средства с микропроцессорным управлением - Макаренко, Ю. В.; Балев, Владимир Николаевич; Маслиев, Вячеслав Георгиевич (НТУ "ХПИ", 2011)
Results over of research of quality of management position of basket are brought in relation to the frame of light cart with the use of regulator of position of basket on a height on the base of microprocessor at a transport vehicle, which is equipped by a pneumatic spring hanging
Keywords: железнодорожный транспорт; пассажирские поезда; комфорт; пневматические рессоры; регулятор положения кузова; транспортные средства